Comparative seismic performance of flat slabs using four design codes - Samsul Abdul Rahman Sidik Hasibuan; Hakas Prayuda; Suraya Hani Adnan; Tengku Anita Raja Hussin; Fredy Kurniawan; Tika Ermita Wulandari (SINERGI, 2026)
This study evaluated the seismic performance of flat slab structures designed according to four international standards: SNI 2847-2019 (Indonesia), NZS 3101:2006 (New Zealand), IS 456-2000 (India), and JSCE 15-2007 (Japan). A five-story reinforced concrete building was modeled using ETABS for nonlinear pushover analysis, while MATLAB was utilized for calculating slab thickness, moment distribution, reinforcement design, and punching shear strength. Results unveiled that the JSCE 15-2007 code provided the stiffest system with minimal lateral displacement and the highest base shear capacity, whereas IS 456-2000 exhibited superior ductility and flexibility. SNI 2847-2019 and NZS 3101:2006 delivered balanced performance in terms of stiffness and material efficiency. The variation in slab thickness, reinforcement area, and natural period highlighted each code’s design philosophy regarding seismic safety. These findings suggest that code selection should consider regional seismic risk, structural demands, and construction priorities to ensure optimal safety and efficiency. The study contributes to the harmonization of global flat slab design practices and offers practical recommendations for improving the seismic resilience of buildings.